Authigenic and Detrital Minerals in Peat Environment of Vasyugan Swamp, Western Siberia† - Rudmin M. A. Maksim Andreevich; Ruban A. S. Aleksey Sergeevich; Savichev O. G. Oleg Gennadievich; Mazurov A. K. Aleksey Karpovich; Dauletova A. B. Aigerim Bauyrzhanovna; Savinova O. V. Olesya Vyacheslavovna (2018, 2018)
Title screen